Efficient Double Suzuki Cross-Coupling Reactions of 2,5-Dibromo-3-hexylthiophene: Anti-Tumor, Haemolytic, Anti-Thrombolytic and Biofilm Inhibition Studies - Ikram , Hafiz Mansoor; Rasool, Nasir; Zubair, Muhammad; Khan, Khalid Mohammed; Chotana, Ghayoor Abbas; Akhtar, Muhammad Nadeem; Nadiah, Abu; Noorjahan Banu, Alitheen; Elgorban, Abdallah Mohamed; Rana, Usman Ali (MDPI - Open Access Publishing, 2016)
The present study describes several novel 2,5-biaryl-3-hexylthiophene derivatives (3a-i) synthesized via a Pd(0)-catalyzed Suzuki cross-coupling reaction in moderate to good yields. The novel compounds were also analyzed for their anti-thrombolytic, haemolytic, and biofilm inhibition activities. In addition, the anti-tumor activity was also evaluated in vitro for newly-synthesized compounds, where 3-hexyl-2,5-bis(4-(methylthio)phenyl)thiophene exhibited the best anti-tumor activity against 4T1 cells with IC50 value of 16 μM. Moreover, 2,5-bis(4-methylphenyl)-3-hexylthiophene showed the highest activity against MCF-7 cells with an IC50 value of 26.2 μM. On the other hand, the compound 2,5-bis(4-chloropheny)-3-hexylthiophene exhibited excellent biofilm inhibition activity. Furthermore, the compound 2,5-bis(3-chloro-4-fluorophenyl)-3-hexylthiophene also exhibited better anti-thrombolytic and hemolytic activity results as compared to the other newly-synthesized compounds.